2011
DOI: 10.12659/msm.881854
|View full text |Cite
|
Sign up to set email alerts
|

Association of MMP1-1607 1G/2G and TIMP1 372 T/C gene polymorphisms with risk of primary open angle glaucoma in a Polish population

Abstract: SummaryBackgroundPrimary open angle glaucoma (POAG) is considered to be a leading cause of irreversible blindness worldwide. Matrix metalloproteinases (MMPs) and their inhibitors (TIMPs) have been extensively studied as POAG risk factors. Recently, several single-nucleotide polymorphisms (SNPs) for MMPs and TIMPs encoding genes have been reported in POAG patients. The aim of this study was to investigate association of the −1607 1G/2G MMP1 and 372 T/C TIMP1 gene polymorphisms with risk of POAG in a Polish popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
(24 reference statements)
1
10
0
1
Order By: Relevance
“…An association of the 2G/2G genotype and 2G allele that we found with POAG occurrence in researched group seems to be in agreement with previously presented studies. Our preliminary results obtained earlier for MMPs polymorphisms have been confirmed (Majsterek et al. 2011).…”
Section: Discussionsupporting
confidence: 79%
“…An association of the 2G/2G genotype and 2G allele that we found with POAG occurrence in researched group seems to be in agreement with previously presented studies. Our preliminary results obtained earlier for MMPs polymorphisms have been confirmed (Majsterek et al. 2011).…”
Section: Discussionsupporting
confidence: 79%
“…78,79,138,144,148 Significant association was found in the overall populations in allelic (OR 1.33, 95% CI: 1.13-1.57; P ¼ 0.54, I 2 ¼ 0.00), homozygote (OR 1.61, 95% CI: 1.05-2.45; P ¼ 0.53, I 2 ¼ 0.00), heterozygote (OR 1.32, 95% CI: 1.08-1.62; P ¼ 0.95, I 2 ¼ 0.00), and dominant comparisons (OR 1.37, 95% CI: 1.12-1.66; P ¼ 0.80, I 2 ¼ 0.00), but not in the recessive model ( 65,72,77,82,84,85,115 For SNP rs1799750 in the MMP gene, four studies (885 POAG cases and 875 controls) were involved. 94,95,104,121 The pooled results showed that rs1799750 was significantly correlated with POAG in recessive model (OR 1.64, 95% CI: 1.05-2.56; P ¼ 0.01, I 2 ¼ 73. 90).…”
Section: Meta-analysis Of the Genetic Association With Poagmentioning
confidence: 99%
“…SNP 372 T/C in the TIMP1 gene was reported in two studies, involving a total of 451 POAG cases and 509 controls. 94,104 Significant association was found in the overall populations in the recessive model (OR 1.50, 95% CI: 1.12-2.01; P ¼ 0.69, I 2 ¼ 0.00, Table 2, Supplementary Files S11).…”
Section: Meta-analysis Of the Genetic Association With Poagmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several single-nucleotide polymorphisms (SNPs) for MMP-encoding genes have been reported in POAG patients. A statistically significant increase in the occurrence of 2G/2G genotype as well as in 2G allele frequency of MMP1 could be observed in POAG patients compared to healthy controls (Majsterek et al, 2011).…”
Section: Discussionmentioning
confidence: 81%